The impact of right ventricular function assessed by 2-dimensional speckle tracking echocardiography on early mortality in patients with inferior myocardial infarction - ÇİNÇİN, AHMET ALTUĞ; KEPEZ, ALPER; ÖZBEN SADIÇ, BESTE; ATAŞ, HALİL; SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT (WILEY, 2018)
BackgroundRight ventricular (RV) involvement in inferior myocardial infarction (MI) increases in-hospital morbidity and mortality. HypothesisRV systolic dysfunction assessed by 2-dimensional speckle tracking echocardiography (STE) might be a predictor of early mortality in patients with acute inferior MI. MethodsEighty-one consecutive patients with acute inferior MI (mean age, 60.812.7years; 18 females) were included. RV myocardial involvement was defined as an elevation >1mm in V-1 or V4R within 12hours of symptom onset. RV function was assessed by STE. Patients were followed for 30days for all-cause mortality. ResultsThirty-eight patients had RV myocardial involvement, and they had significantly lower tricuspid annular plane systolic excursion (TAPSE), tricuspid annular systolic velocity (RVS), and left ventricular (LV) and RV global longitudinal strain (GLS). Nine patients (11%) died within 30days. The mean age of mortality group was higher with more female frequency. They had significantly higher pro-BNP, hs-troponin T, and creatinine levels, but lower hemoglobin levels. TIMI 3 flow was significantly less achieved in mortality group. RV myocardial involvement was more frequent in the mortality group, and they had significantly lower TAPSE, RVS, and LV and RV GLS. Multivariate analysis revealed that age and RV GLS were independent predictors of early mortality. RV GLS -14% predicted early mortality in patients with acute inferior MI with a sensitivity of 88.9% and a specificity of 62.5% (AUC: 0.817, P =0.002). ConclusionsRV GLS may be useful in predicting early mortality in patients with acute inferior MI.
Keywords: Inferior Myocardial Infarction; Mortality; Right Ventricular Function; Speckle Tracking Echocardiography; ST-SEGMENT ELEVATION; HEART-FAILURE; INVOLVEMENT; STRAIN; PATHOPHYSIOLOGY; DYSSYNCHRONY; DISEASE